Penerapan Media Pop-Up Book Digital Berbasis Etnosains untuk Meningkatkan Literasi Sains Siswa Kelas IV Mata Pelajaran IPAS SD Muhammadiyah Lamongan - Abdul Muiz; A. F. Suryaning Ati MZ; Linaria Arofatul Ilmi Uswatun Khasanah (Mataram University, 2026)
The low science literacy of Grade IV students at SD Muhammadiyah Lamongan served as the background of this study. Initial observations revealed that only 30% of students met the Learning Objective Achievement Criteria (KKTP), while the media used were still limited to Canva, PowerPoint, and simple videos that lacked interactivity. This study aimed to describe teacher activity, student activity, and the improvement of science literacy through the implementation of ethnoscience-based digital Pop-Up Book media in the IPAS subject. This study employed a Classroom Action Research (CAR) design conducted in two cycles, involving 20 students of Grade IV D at SD Muhammadiyah Lamongan. Data were collected through teacher and student activity observation sheets, as well as essay-based science literacy tests. The results showed significant improvements across all measured aspects. Teacher activity increased from 52% in Cycle I to 91% in Cycle II. Student activity increased from 55% in Cycle I to 92% in Cycle II. Students' science literacy achievement rose from 40% in Cycle I to 85% in Cycle II. It is therefore concluded that the implementation of ethnoscience-based digital Pop-Up Book media effectively improves the science literacy of Grade IV students in the IPAS subject at SD Muhammadiyah Lamongan.